Guide to wireless communications - Olenewa, Jorge (Course Technology, Cengage Learning, 2014)
Covers the fundamentals wireless communications and provides an overview of protocols, transmission methods, and IEEE standards. This title covers several technologies for Wireless Personal Area Networks (WPANs), Wireless Local Area Networks (WLANs), Wireless Metropolitan Area Networks (WMANs), and Wireless Wide Area Networks (WWANs).